Anisotropic conductive film based on porous metal conductive microspheres and preparation method thereof

By preparing porous metal conductive microspheres, the problems of unstable conductivity and environmental pollution in high-fine circuit connections are solved, and the stable improvement of conductivity and environmentally friendly high-fine circuit connections are achieved.

CN119661983AActive Publication Date: 2025-03-21NANJING UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411529944.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-03-21
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The existing composite conductive microspheres have problems such as unstable conductivity, limited compression deformation rate, high diameter consistency requirements and environmental pollution in high-fine circuit connections.

Method used

Porous metal conductive microspheres are prepared by preparing alloy micropowder, annealing and separation of ceramic or salt powder, sorting and corrosion treatment by liquid grading technology, and porous metal conductive microspheres with large compression deformation rate and high spherical shape for the preparation of anisotropic conductive films.

Benefits of technology

It has achieved a stable improvement in conductivity, reduced the requirements for the consistency of the diameter of conductive microspheres, reduced the difficulty of sorting, and reduced environmental pollution, and is suitable for high-fine circuit connections.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661983A_ABST
    Figure CN119661983A_ABST
Patent Text Reader

Abstract

The invention discloses an anisotropic conductive film based on porous metal conductive microspheres. The anisotropic conductive film comprises the following raw materials: resin, a latent curing agent or / and a curing agent, a defoaming agent and the porous metal conductive microspheres. The conductive film comprises the following raw materials in parts by weight: 100 parts of resin, 3-10 parts of a latent curing agent, 1-10 parts of a curing agent, 3-15 parts of a defoaming agent and 4-25 parts of porous metal conductive microspheres, particularly, the porous gold conductive microspheres account for 7-20wt% of the weight of the resin matrix. And a preparation method. Comprising the following steps: 1) preparing alloy micro powder; (2) preparing alloy microspheres; (3) sorting the alloy microspheres; and 4) preparing the porous metal conductive microspheres. Compared with a composite conductive microsphere widely used in the current anisotropic conductive film, the porous metal conductive microsphere has a large compression deformation rate, ensures a large contact area and good conductivity, and can meet wide application in the field of electronic packaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an anisotropic conductive film for ultrafine electrode connection and a preparation method thereof, and belongs to the field of electronic packaging materials. Background Art

[0002] Anisotropic conductive film (ACF for short) is widely used in the field of electrical connection between microelectrodes in electronic devices. It is mainly composed of an insulating resin binder and a conductive filler dispersed in the insulating resin binder. The anisotropic conductive function of the conductive film is closely related to the conductive filler present therein. The performance of the conductive filler determines the conductivity and durability of the anisotropic conductive film. From the development of anisotropic conductive films, the conductive fillers that can be used include carbon particles such as carbon black and graphite, metal particles such as copper, nickel, silver, and gold, and polymer composite conductive microspheres with a metal layer coated on the surface. Carbon particles have little deformability during hot pressing, and there is only point contact between the electrodes, so the conductivity is poor. Metal particles are similar to carbon particles. In addition to having little deformability during hot pressing and poor conductivity, their large bulk density makes them prone to sinking and uneven distribution when mixed with resin binders. Composite conductive microspheres outperform carbon and metal particles and are currently widely used. However, several challenges remain. 1) The conductivity of composite conductive microspheres is determined not only by the conductivity of the coating itself but also by the degree of compression deformation during use. A high compression ratio is beneficial for ensuring good conductivity. However, the inner plastic sphere has relatively poor toughness, and large compression deformation can cause cracks or breakage, leading to connection failure. 2) The ideal compression ratio for composite conductive microspheres currently ranges from 6% to 14%. This narrow compression ratio range places high demands on the uniformity of the microsphere diameter, making it difficult to sort the microspheres. 3) As circuits become increasingly sophisticated, the electrode gaps are required to be smaller, and the diameter of the conductive particles used in ACFs is also required to be smaller. Limited by the microsphere deformation ratio, a 3-micron diameter composite conductive microsphere is nearing its minimum diameter limit. Therefore, developing an anisotropic conductive film based on small-diameter conductive particles with high compression ratio, good conductivity, and high conductivity is crucial for achieving high-precision circuit connections. Summary of the Invention

[0003] The object of the present invention is to provide an anisotropic conductive adhesive based on porous metal conductive microspheres (the adhesive can form a conductive film with anisotropic properties when coated) and a preparation method.

[0004] The technical solution of the present invention is an anisotropic conductive film based on porous metal conductive microspheres (coated with conductive glue for subsequent application), wherein the conductive film comprises the following raw materials: resin (especially bisphenol A epoxy resin), latent curing agent and / or curing agent, defoaming agent, and porous metal conductive microspheres.

[0005] The preparation of the porous metal conductive microspheres includes the following steps: Step 1) preparing alloy powder. Alloy refers to an alloy formed by a metal with lower activity and at least one metal with higher activity, and the total atomic ratio of atoms with higher activity in the alloy is in the range of 30% to 95%. Specifically, it includes alloys formed by gold and at least one of silver, copper, tin, and nickel, alloys formed by silver and at least one of copper, zinc, and cadmium, alloys formed by copper and at least one of zinc and cadmium, and alloys formed by nickel and aluminum. Alloy powder can be obtained by chemical methods such as co-precipitation, sol-gel, spray drying (or spray freeze drying) + hydrogen reduction, or physical methods such as smelting + crushing, gas phase condensation, and atomization;

[0006] Step 2) Prepare alloy microspheres. The alloy micropowder is uniformly mixed with ceramic powder or salt powder, annealed at a temperature above the melting point of the alloy, and separated from the ceramic or salt powder after cooling to obtain spherical alloy micropowder. The ceramic powder refers to high-melting-point oxides or nitrides, or mixtures thereof, and the salt refers to chloride salts. The mass ratio of the alloy micropowder to the ceramic powder should be such that the alloy micropowder can be separated from the ceramic powder or salt powder.

[0007] Step 3) sorting the alloy microspheres. The average diameter of the sorted alloy microspheres is in the range of 1 μm to 80 μm;

[0008] Step 4) preparing porous metal conductive microspheres. Specifically, the sorted alloy microspheres are corroded in an acid or alkaline solution to remove the highly active metals, thereby obtaining porous metal conductive microspheres of gold, silver, copper, or nickel, wherein the porosity of the porous metal conductive microspheres is in the range of 30% to 95%.

[0009] Furthermore, in the preparation step 3) of the porous metal conductive microspheres, the alloy microspheres are sorted by liquid classification technology to obtain alloy microspheres with the desired average diameter and classification accuracy. The average diameter of the alloy microspheres is in the range of 1μm to 80μm, and the preferred average diameter is in the range of 1μm to 40μm. When the average diameter is less than or equal to 2μm, the classification accuracy is less than or equal to 1μm; when the average diameter is greater than 2μm and less than or equal to 4μm, the classification accuracy is less than or equal to 2μm; when the average diameter is greater than 4μm and less than or equal to 7μm, the classification accuracy is less than or equal to 4μm; and when the average diameter is greater than 7μm, the classification accuracy is less than or equal to 6μm.

[0010] Furthermore, the conductive film comprises the following raw materials by weight: 100 parts resin, 3-10 parts latent curing agent, 1-10 parts curing agent, 3-15 parts defoaming agent, 4-25 parts porous metal conductive microspheres. A more preferred range is: the porous gold conductive microspheres account for 7-20 wt% of the weight of the resin matrix.

[0011] Furthermore, a method for preparing an anisotropic conductive film based on porous metal conductive microspheres comprises the following steps:

[0012] 1) Mechanically stirring the resin, latent curing agent, curing agent, defoaming agent, and inactive diluent, and ultrasonically dispersing them until uniform, then adding the porous metal conductive microspheres, vacuuming to remove bubbles, and then mechanically stirring and ultrasonically dispersing them to obtain anisotropic conductive adhesive;

[0013] 2) Pre-curing the anisotropic conductive adhesive at 60-80° C. for 10-20 min, degassing, and then coating the film to a thickness of 3-150 μm. The resulting film is further cured at room temperature for 6-12 h to obtain an anisotropic conductive film.

[0014] Beneficial effects: Anisotropic conductive films are widely used in the field of electrical connection between microelectrodes of electronic devices. They are mainly composed of an insulating resin binder and conductive particles dispersed in the insulating resin binder. The anisotropic conductive function of the conductive film is closely related to the conductive particles present therein. The performance of the conductive particles determines the conductivity and durability of the anisotropic conductive film. Compared with composite conductive microspheres, the porous metal conductive microspheres manufactured by the present invention have the following advantages: a large compression deformation rate, which ensures a large contact area and good conductive performance; there is no breakage during crimping interconnection, which can increase the pressure range during crimping interconnection and reduce the difficulty of operation during crimping interconnection (the pressure direction is electrically connected to each other, and the direction perpendicular to this direction is the state of resin insulation, that is, it has anisotropic conductivity); a large compression deformation rate reduces the requirements for the consistency of the microsphere diameter size, and reduces the difficulty of sorting the microspheres; no chemical plating process is required, which reduces the impact on the environment. The porous metal conductive microspheres manufactured by the present invention have high sphericity, controllable average diameter and diameter distribution range, and the prepared anisotropic conductive film has obvious advantages in the interconnection of fine-pitch circuits and can meet the wide application in the field of electronic packaging. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 Scanning electron microscope photograph of spherical gold-copper alloy particles obtained by liquid sorting method, with a particle size distribution of 4.5 to 10.5 μm and an average particle size of 7.53 μm;

[0016] Figure 2Scanning electron micrograph of porous gold microspheres after chemical dealloying of gold-copper alloy spherical particles (a on the left) and a high-magnification scanning electron micrograph (b on the right);

[0017] Figure 3 Optical microscope photographs of the surface of conductive film 1 (left image, a) and the surface of commercial AC-3514 anisotropic conductive film (right image, b);

[0018] Figure 4 Schematic diagram of the four-terminal method for measuring the connection resistance of anisotropic conductive film;

[0019] Figure 5 Curves of connection resistance of three types of anisotropic conductive films measured by four-terminal method versus pressure;

[0020] Figure 6 Scanning electron microscope photographs of the commercial AC-3514 conductive film and conductive film 1 viewed from above after hot pressing at binding pressures of 0.1 MPa, 0.3 MPa, and 0.5 MPa: (A), (B), and (C) are commercial AC-3514 conductive films, and (D), (E), and (F) are conductive film 1. DETAILED DESCRIPTION

[0021] The present invention will be further described below with reference to specific examples, but the present invention is not limited to the contents of the specification. All the reagents used below were analytically pure.

[0022] The conductive film raw materials include: resin, latent curing agent, curing agent, defoaming agent, and porous metal conductive microspheres. The porous metal conductive microspheres in this invention are prepared by the following method. First, alloy powder is prepared. The alloy powder is then uniformly mixed with ceramic or salt powder. The mixture is annealed at a temperature above the melting point of the alloy. The non-wetting property of the alloy droplets at the ceramic or salt solid interface is utilized to form alloy spherical droplets. After cooling, the ceramic or salt powder is removed to obtain alloy spherical micropowder. Liquid sorting is then performed to obtain alloy spherical micropowder of the desired diameter. Finally, the alloy spherical micropowder is reacted with an acid or base to corrode the active elements in the alloy through a dealloying process, resulting in porous metal conductive microspheres. The porous metal conductive microsphere powder is uniformly mixed with the resin, latent curing agent, curing agent, and defoaming agent to prepare an anisotropic conductive adhesive. The anisotropic conductive adhesive is pre-cured and degassed at 60-80°C, and then coated. The resulting film is further cured at room temperature for 10-12 hours to obtain an anisotropic conductive film.

[0023] Example 1 Preparation of Porous Gold Conductive Microspheres with a Porosity of 80% and an Anisotropic Conductive Film

[0024] A chloroauric acid solution and a copper nitrate solution were measured and mixed in a gold to copper atomic ratio of 1:4. An appropriate amount of solid sodium chloride was added and thoroughly sonicated to dissolve and disperse the mixture. The mixed solution was spray-freeze dried to obtain a uniformly distributed gold-copper mixture / sodium chloride precursor. This mixture was then placed in a muffle furnace at 450°C for 15 minutes. The precursor mixture was then heated at 700°C in a hydrogen atmosphere tube furnace for 40 minutes. This process was repeated two to three times and then washed to obtain an irregular gold-copper alloy powder with a particle size distribution of 0.5 to 10 μm. The irregular gold-copper alloy powder was mechanically mixed with boron nitride powder, heated to 1180°C in a hydrogen atmosphere tube furnace, and annealed for 20 minutes. The mixture was then cooled to room temperature and washed to remove the dispersant. This yielded a uniform gold-copper alloy spherical micropowder with a particle size distribution of 2 to 13 μm.

[0025] The prepared gold-copper alloy spherical powder was sorted by liquid classification technology, and the alloy spherical powder of 4.5-10.5 μm (such as Figure 1 ). The separated alloy spherical powder is dispersed in a certain amount of deionized water, and 20% wt (of the powder mass) of PVP is added. Ultrasound is used to ensure that the particles are fully dispersed. Then, an appropriate amount of concentrated nitric acid is added to the liquid, and the concentration of nitric acid is adjusted to 7.5 mol / L. The temperature is kept at 50°C for 24 hours, and the sample is repeatedly washed with deionized water to obtain porous gold spherical powder (such as Figure 2 In order to remove stress and defects, the porous gold spherical powder was annealed at 300° C. for 30 minutes, and the annealed porous gold spherical powder was used for the subsequent preparation of anisotropic conductive films.

[0026] Preparation of anisotropic conductive film: Step 1, E44 and E51 epoxy resins are mixed in a ratio of 1:4, an appropriate amount of anhydrous ethanol (accounting for 10% wt of the E44 / E55 resin matrix) is added to activate the epoxy resin matrix, and then an appropriate amount of defoaming agent (accounting for 5% wt of the E44 / E55 resin matrix) is added to remove bubbles, and the mixture is fully stirred for standby use; Step 2, a low molecular weight polyamide resin curing agent (accounting for 9% wt of the E44 / E55 resin matrix) and 2-methylimidazole (accounting for 3% wt of the E44 / E55 resin matrix) are dissolved in an appropriate amount of anhydrous ethanol (accounting for 10% wt of the E44 / E55 resin matrix) according to the proportion. , stir and dissolve thoroughly for later use; step 3, place the porous gold spherical powder accounting for 5% wt (volume percentage is about 1.17%) of the E44 / E55 resin matrix in an appropriate amount of anhydrous ethanol, fully ultrasonically disperse and set aside; step 4, first slowly drip the mixed solution of step 3 into the epoxy resin matrix of step 1, and after vacuum degassing for 30 minutes, add the mixed solution of step 2 to the above epoxy resin glue, mechanically stir for 10-15 minutes and set aside; step 5, place the mixed glue of step 4 in a 60-degree oven for curing for 20 minutes, then raise the temperature to 80 degrees, and take out the glue after curing for 2 minutes for degassing. Adjust the parameters of the wet film device, manually apply the above glue on the PET film at a speed of 5 cm per second, and place it at room temperature for 12 hours after cooling to obtain an anisotropic conductive film with a thickness of 20 μm, called conductive film 1. The optical microscope photo of the surface of conductive film 1 is as follows. Figure 3 As shown in the left picture.

[0027] Example 2 Preparation of porous conductive gold microspheres and anisotropic conductive film with a porosity of 90%: According to the atomic ratio of gold to copper of 1:9, chloroauric acid solution and copper nitrate solution were measured and mixed evenly, and an appropriate amount of sodium chloride solid was added and fully ultrasonically dissolved and dispersed. The mixed solution was spray-freeze dried to obtain a relatively uniformly distributed gold-copper mixture / sodium chloride precursor. The gold-copper mixture / sodium chloride precursor was placed in a 450°C muffle furnace and kept warm for 15 minutes. The mixture precursor was then kept warm at 700°C in a hydrogen atmosphere tube furnace for 40 minutes. After repeating this process 2-3 times, it was washed to obtain an irregular gold-copper alloy powder with a particle size distribution between 0.5 and 10 μm. The irregular gold-copper alloy powder was mechanically mixed with boron nitride powder, heated to 1180°C in a hydrogen atmosphere tube furnace and annealed for 20 minutes. The mixture was then cooled to room temperature with the furnace, and the dispersant was washed and stripped to obtain a gold-copper alloy spherical micropowder with uniform composition and a particle size distribution between 2 and 12 μm.

[0028] The prepared gold-copper alloy spherical micropowder is sorted by liquid classification technology, and the alloy spherical micropowder of 5 to 10 μm is selected. The sorted alloy spherical micropowder is dispersed in a certain amount of deionized water, and 30% wt (of the powder mass) of PVP is added, and ultrasound is used to ensure that the particles are fully dispersed. Then, an appropriate amount of concentrated nitric acid is added to the liquid, and the acid concentration is adjusted to 4 mol / L. The dealloying is carried out at room temperature for 2 hours, and then the nitric acid concentration is increased to 7.5 mol / L, and the temperature is increased to 50°C and kept constant for 24 hours. The sample is then repeatedly washed with deionized water to obtain porous gold spherical powder. In order to remove stress and defects, the porous gold spherical powder is annealed at 300°C for 30 minutes. The annealed porous gold spherical micropowder is used for the subsequent preparation of anisotropic conductive film.

[0029] Preparation of anisotropic conductive film: Step 1, E44 and E51 epoxy resins are mixed in a ratio of 1:4, an appropriate amount of anhydrous ethanol (accounting for 10% wt of the E44 / E55 resin matrix) is added to activate the epoxy resin matrix, and then an appropriate amount of defoaming agent (accounting for 5% wt of the E44 / E55 resin matrix) is added to remove bubbles, and the mixture is fully stirred for standby use; Step 2, a low molecular weight polyamide resin curing agent (accounting for 9% wt of the E44 / E55 resin matrix) and 2-methylimidazole (accounting for 3% wt of the E44 / E55 resin matrix) are dissolved in an appropriate amount of anhydrous ethanol (accounting for 1% wt of the E44 / E55 resin matrix) according to the proportion. 10% wt), fully stirred and dissolved for later use; Step 3, place the porous gold conductive microspheres accounting for 10% wt of the weight of the E44 / E55 resin matrix in an appropriate amount of anhydrous ethanol, fully ultrasonically disperse and set aside; Step 4, first slowly drip the mixed solution of Step 3 into the epoxy resin matrix of Step 1, after vacuum degassing for 30 minutes, add the mixed solution of Step 2 to the above-mentioned epoxy resin glue, mechanically stir for 10-15 minutes and set aside; Step 5, place the mixed glue of Step 4 in a 60-degree oven to cure for 20 minutes, then raise the temperature to 80 degrees, and after curing for 2 minutes, remove the glue and degas. Adjust the parameters of the wet film device, manually apply the above-mentioned glue on the PET film at a speed of 15 cm per second, and after cooling, place it at room temperature for 12 hours to obtain an anisotropic conductive film with a thickness of 30 μm, which is called conductive film 2.

[0030] Comparative Example

[0031] The comparison conductive film is a purchased anisotropic conductive film with polystyrene microspheres as the core layer and composite conductive microspheres made by roughening, sensitization, activation and chemical plating of Ni / Au as conductive fillers. The brand is: Korean Trefos AC-3514, and the diameter of the composite conductive microspheres is 5μm. Figure 3 The right picture in the figure is an optical microscope photograph of the surface of the commercial AC-3514 anisotropic conductive film. It can be seen that the number of conductive particles in the composite conductive microspheres in the AC-3514 conductive film is significantly higher than the number of porous gold conductive microspheres in the conductive film 1.

[0032] Conductivity test:

[0033] use Figure 4 The circuit connections shown are used to measure the connection resistance of the package sample (a PCB board (L*W: 9*8mm, thickness 0.8mm) with copper pads with a spacing of 1000μm) using the four-terminal method. Figure 5 The following graph shows the relationship between the connection resistance of three different samples and pressure. The graph shows that the connection resistance of the commercial AC-3514 is very sensitive to pressure. When the pressure is less than 0.2 MPa, the connection resistance is relatively high (greater than 100 mΩ). As the pressure increases, the resistance gradually decreases, reaching a minimum of 13.1 mΩ at 0.3 MPa. After that, the resistance begins to gradually increase as the pressure increases further. Therefore, the actual pressure range for the commercial AC-3514 is relatively narrow. The test results show that the connection resistance is relatively low in the range of 0.2 to 0.4 MPa, with a resistance below 20 mΩ. This test result is consistent with the packaging pressure range provided by the manufacturer.

[0034] Conductive Film 1 and Conductive Film 2 both exhibit excellent electrical conductivity. Their connection resistance is below 20mΩ, which is comparable to the connection resistance of the commercial AC-3514 package within the normal pressure range (0.2-0.4MPa). The number of conductive particles used in Conductive Film 1 and Conductive Film 2 is significantly less than that in the commercial AC-3514. The lower connection resistance is mainly due to the large compression deformation of the porous gold microspheres ( Figure 6 ) brings large contact area and short connection distance.

[0035] The lateral connection resistance of commercial AC-3514, conductive film 1 and conductive film 2 was measured using the two-terminal method. The results are shown in Table 1. When the pressure of commercial AC-3514 is 0.4 MPa or less, the connection resistance is greater than 10 9 Ω, when the pressure is equal to or higher than 0.5MPa, the resistance is less than 10 8 Ω, causing connection failure (horizontal connection resistance <10 8 Ω considered lateral connection failure), and some particles broke under high pressure ( Figure 6 C). However, the lateral connection resistance of conductive film 1 and conductive film 2 is greater than 10 within the measured pressure range. 9 Ω, no connection failure will occur.

[0036] Table 1. Variation of lateral connection resistance of three anisotropic conductive films with pressure

[0037]

[0038] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, any modifications and improvements made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. Anisotropic conductive film based on porous metal conductive microspheres, characterized in that: The anisotropic conductive film comprises the following raw materials: resin, latent curing agent or / and curing agent, defoaming agent, and porous metal conductive microspheres.

2. The anisotropic conductive film based on porous metal conductive microspheres according to claim 1, characterized in that: The conductive film comprises the following raw materials in parts by weight: 100 parts of resin, 3-10 parts of latent curing agent, 1-10 parts of curing agent, 3-15 parts of defoaming agent, 4-25 parts of porous metal conductive microspheres; the porous gold conductive microspheres account for 7-20wt% of the weight of the resin matrix.

3. The preparation of anisotropic conductive film based on porous metal conductive microspheres according to claim 1 or 2, characterized in that: The steps include: Step 1) preparing alloy powder; alloy refers to an alloy formed by a metal with lower activity and at least one metal with higher activity, and the total atomic ratio of atoms with higher activity in the alloy is in the range of 30% to 95%; specifically including alloys formed by gold and at least one of silver, copper, tin, and nickel, alloys formed by silver and at least one of copper, zinc, and cadmium, alloys formed by copper and at least one of zinc and cadmium, and alloys formed by nickel and aluminum; alloy powder can be prepared by coprecipitation, sol-gel, spray drying + hydrogen reduction, or smelting + crushing, gas phase condensation, atomization physical methods; Step 2) preparing alloy microspheres; the alloy micropowder is uniformly mixed with ceramic powder or salt powder, annealed at a temperature above the melting point of the alloy, and separated from the ceramic or salt powder after cooling to obtain alloy spherical micropowder; the ceramic powder refers to high melting point oxides or nitrides and their mixtures, and the salt refers to chloride salt; the mass ratio of the alloy micropowder to the ceramic powder should satisfy the requirement that the alloy micropowder can be isolated by the ceramic powder or salt powder; Step 3) sorting the alloy microspheres; the average diameter of the sorted alloy microspheres is in the range of 1 μm to 80 μm; Step 4) preparing porous metal conductive microspheres; specifically, corroding the sorted alloy microspheres in an acid or alkaline solution to corrode the highly active metal to obtain porous metal conductive microspheres of gold, silver, copper or nickel, wherein the porosity of the porous metal conductive microspheres is in the range of 30% to 95%.

4. The method according to claim 3, characterized in that: In the preparation step 3) of the porous metal conductive microspheres, the alloy microspheres are sorted by liquid classification technology to obtain alloy microspheres with the required average diameter and classification accuracy; the average diameter of the alloy microspheres is in the range of 1μm to 40μm; when the average diameter is less than or equal to 2μm, the classification accuracy is less than or equal to 1μm; when the average diameter is greater than 2μm and less than or equal to 4μm, the classification accuracy is less than or equal to 2μm; when the average diameter is greater than 4μm and less than or equal to 7μm, the classification accuracy is less than or equal to 4μm; when the average diameter is greater than 7μm, the classification accuracy is less than or equal to 6μm.

5. The method according to claim 3, characterized in that: The conductive film comprises the following raw materials in parts by weight: 100 parts of resin, 3-10 parts of latent curing agent, 1-10 parts of curing agent, 3-15 parts of defoaming agent, and 4-25 parts of porous metal conductive microspheres.

6. The method for preparing anisotropic conductive film based on porous metal conductive microspheres according to any one of claims 3 to 5, characterized in that: The method comprises the following steps: 1) mechanically stirring the resin, latent curing agent, curing agent, defoaming agent and inactive diluent, ultrasonically dispersing the resin until uniform, adding the porous metal conductive microspheres, vacuuming to remove bubbles, and then mechanically stirring and ultrasonically dispersing the porous metal conductive microspheres to obtain anisotropic conductive adhesive; 2) Pre-curing the anisotropic conductive adhesive at 60-80° C. for 10-20 min, degassing, and then coating with a film thickness of 3-150 μm. The obtained film is further cured at room temperature for 6-12 h to obtain an anisotropic conductive film.

Citation Information

Patent Citations

  • Flexible conductive microballoon and applications thereof

    CN105070351A

  • Anisotropic conductive adhesive based on liquid metal-porous microsphere skeleton and preparation method thereof

    CN114933867A

  • Anisotropically conductive film

    JP1993117419A

  • Anisotropic conductive film and electronic apparatus using the same

    JP2006252980A

  • Anisotropic conductive film and manufacturing method thereof

    KR1020150098179A